Improving Students’ Vocabulary Mastery through Visual Crossword Puzzle at SD Islam Al-Jidsi - Saepuloh, Asep; Suryani, Yeni; Diningsih, Cinde Adia; Sulistiyani, Adinda (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2022)
The studies regarding the effectiveness of teaching using a mobile phone on students’ vocabulary mastery are widely discussed. While the process of how students acquire that vocabulary from a mobile phone is barely touched. That’s why the purpose of this study is to investigate the process of students acquiring English vocabulary from mobile phone use and whether the students comprehend the meaning of the vocabulary that they acquire or not. The design of this study employed study case design. The subject of this study was 7 students at a fourth-grade elementary school. The observation and interview were used for data collection. The research results demonstrated that mobile phone has great potential as an instructional tool for acquiring English vocabulary. The findings also indicated that the process of acquiring English vocabulary is caused by two factors. The first is psycholinguistic factors and the second is social factors. The finding indicated that the psycholinguistic factors hold the significant one. It can be seen from the repetition and exploration done by their own self in acquiring the English vocabulary. While the social factor such as people around them (their parents and friends) have less contribution in assisting them in acquiring the English vocabulary. Regarding the comprehension of vocabulary that they acquired, the findings suggested that three students understand and know the real meaning of most of the English vocabulary that they gained from daily mobile phone use, while the rest (four) students knew the words only based on words function without knowing the real meaning of each English word. Generally, findings clearly showed that mobile phones facilitated students in acquiring English vocabulary independently.